Experimental study of micromechanical properties alterations of shale matrix treated by ScCO2-Water saturation using nanoindentation tests. (1st March 2022) - Cheng, P.; Zhang, C.P.; Ma, Z.Y.; Zhou, J.P.; Zhang, D.C.; Liu, X.F.; Chen, H.; Ranjith, P.G.
Abstract: Supercritical CO2 (ScCO2 ) fracturing is a preferred alternative to water-based fracturing for stimulation of the shale gas reservoirs, and also promotes CO2 geological sequestration. The injected ScCO2 will interact with shale minerals and then induce changes in rock matrix micromechanics. In this study, a series of nanoindentation tests was conducted on the shale sample to investigate the effects of ScCO2 -water treatment on shale matrix micromechanics. X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy-dispersive spectroscopy (EDS) were used to analyze the changing mechanisms of micromechanical properties. The dispersion of grid nanoindentation data of different minerals indicates the strong heterogeneity of shale' micromechanical properties. After ScCO2 -water treatment, different shale minerals experienced different reductions of Er and H because of the dissolution induced the alterations in crystal structures, and their contents also altered in varying degrees. The values of h f / h m and W p / W t can be combined with the hysteresis loops enclosed by the P-h curves to determine the dominant work and irreversible deformation that produced in the process of indentation. According to the observation of indentation morphology, unlike other minerals, considerable micro-fractures were generated in clay minerals, which is correlated to the significant plastic deformation and the layered crystal structure. Highlights: Nanoindentation method was applied for evaluating micromechanical heterogeneity of shale matrix. After treated with ScCO2 -water, the micromechanical properties of different shale minerals decreased except for quartz. Considerable micro-fractures were generated in clay minerals because of weak mechanical strength and layered structures.